Sentinel Node Procedure to Select Clinically Localized Prostate Cancer Patients with Occult Nodal Metastases for Whole Pelvis Radiotherapy - Hilda A. de Barros; Jan J. Duin; Daan Mulder; Vincent van der Noort; M. Arjen Noordzij; Esther M.K. Wit; Floris J. Pos; Wouter V. Vogel; Eva E. Schaake; Fijs W.B. van Leeuwen; Pim J. van Leeuwen; Nikolaos Grivas; et al. (European Urology Open Science, 2023)
Background: Accurate identification of men who harbor nodal metastases is necessary to select patients who most likely benefit from whole pelvis radiotherapy (WPRT). Limited sensitivity of diagnostic imaging approaches for the detection of nodal micrometastases has led to the exploration of the sentinel lymph node biopsy (SLNB). Objective: To evaluate whether SLNB can be used as a tool to select pathologically node-positive patients who likely benefit from WPRT. Design, setting, and participants: We included 528 clinically node-negative primary prostate cancer (PCa) patients with an estimated nodal risk of >5% treated between 2007 and 2018. Intervention: A total of 267 patients were directly treated with prostate-only radiotherapy (PORT; non-SLNB group), while 261 patients underwent SLNB to remove lymph nodes directly draining from the primary tumor prior to radiotherapy (SLNB group); pN0 patients were treated with PORT, while pN1 patients were offered WPRT. Outcome measurements and statistical analysis: Biochemical recurrence–free survival (BCRFS) and radiological recurrence-free survival (RRFS) were compared using propensity score weighted (PSW) Cox proportional hazard models. Results and limitations: The median follow-up was 71 mo. Occult nodal metastases were found in 97 (37%) SLNB patients (median metastasis size: 2 mm). Adjusted 7-yr BCRFS rates were 81% (95% confidence interval [CI] 77–86%) in the SLNB group and 49% (95% CI 43–56%) in the non-SLNB group. The corresponding adjusted 7-yr RRFS rates were 83% (95% CI 78–87%) and 52% (95% CI 46–59%), respectively. In the PSW multivariable Cox regression analysis, SLNB was associated with improved BCRFS (hazard ratio [HR] 0.38, 95% CI 0.25–0.59, p < 0.001) and RRFS (HR 0.44, 95% CI 0.28–0.69, p < 0.001). Limitations include the bias inherent to the study’s retrospective nature. Conclusions: SLNB-based selection of pN1 PCa patients for WPRT was associated with significantly improved BCRFS and RRFS compared with (conventional) imaging-based PORT. Patient summary: Sentinel node biopsy can be used to select patients who will benefit from the addition of pelvis radiotherapy. This strategy results in a longer duration of prostate-specific antigen control and a lower risk of radiological recurrence.